Exploring Problems and Opportunities in Using Social Media A Community Program for Senior High School Students - Yogi Saputra Mahmud (Ilin Institute, 2021)
Social media is an inseparable aspect of young generations who are considered digital natives or individuals who live in the middle of the digital era. Moreover, the use of social media becomes a significant activity for young generations to create content, communicate, and explore information in real-time without physical, geographical, and temporal borders. Despite this, the massive use of social media by young generations, including senior high school students, is not always in accordance with the level of digital literacy and communication ethics in social media. This phenomenon eventually leads to some adverse drawbacks. Based on these statements, therefore, this community empowerment program aims to provide an understanding of digital literacy and to explore the problems and opportunities in using social media for senior high school students in Indonesia. There were around 474 participants who were involved in this community empowerment program, including the students of SMA Negeri 2 Bondowoso, SMA YPPK Agustinus Kota Sorong, and the International Relations study program President University. The result from a survey revealed that the majority of participants had experienced problems in using social media, including addiction, cybercrime, cyberbullying, exposure to adult content, and many others. Some recommendations and suggestions for relevant programs in the future are also outlined in this paper to improve students' digital literacy and communication ethics in social media.